Frozen Section Versus Permanent Section in Cancer Diagnosis: A Single Centre Study - Bharadwaj, Barasha Sarma; Deka, Muktanjalee; Salvi, Manisha; Das, B K; Goswami, B C (Asian Pacific Journal of Cancer Care, 2022)
Introduction: Frozen section is an intraoperative pathological technique which has very important role to play in diagnostics and also it plays important role in futher surgical management as specially in oncology setup. Most common indications for frozen section were confirmation of neoplasms, evaluation of margins status, evaluation of metastasis etc. Materials and Methods: This is a prospective study of 200 frozen section cases, where frozen sections were compared with permanent Haematoxylin and Eosin stained slides. Accuracy of frozen sections were analysed with various parameters like true positive, false positive, sensitivity, specificity, concordance rate etc. Results: Highest number cases were from gall bladder/ biliary tract (45) followed by breast tissue (43), lymph node (32) etc. Diagnostic accuracy of frozen section was 95.5% (191/200 cases) when compared with permanent section. Concordance rate was 191 (95.5%), sensitivity 89.5% with positive predictive value 96.7% and negative predictive value 94.9% respectively. Conclusion: Adequate and accurate sampling is recommended and also interpretation error should be minimized to help reducing the rate of discordant cases.